Physical Chemistry Of Slag-Metal Reactions (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1951)
BASIC open-hearth slags have no obviously unique features when compared with slags from other metallurgical operations. Open-hearth slags form and exist at temperatures ranging from 2500 to 3100 F (1370 to 1700 C). In the course of an open-hearth heat, the liquid slag changes slowly and continuously in chemical analysis-the changes reflecting changes in temperature, changes in metal analysis, solution of charged materials, solution of feed additions, and solution of refractories. Through- out the process, the slag performs specific primary functions that are responsible for a large measure of the technical and economic importance of basic open-hearth steelmaking. It is intended in this chapter to present the chemical reactions by which the primary functions of basic open-hearth slags are carried out, to describe the physical and chemical principles governing the extent to which these reactions proceed and can be regulated, and finally to indicate the limitations imposed on other features of the process by the fulfillment of the primary functions. Basic open-hearth slags perform three primary functions. First and foremost, the slag provides a means of removing phosphorus from the liquid metal. The ability to remove phosphorus is largely responsible for the widespread use of the basic open- hearth process. Second, the slag serves as a controlling factor in transferring the oxygen required for the other oxidizing reactions. Third, the slag provides a means of eliminating some sulfur from the open-hearth bath. While the extent of sulfur removal is not comparable to that of phosphorus, the ability to remove some sulfur contributes much to the value of the process. The effectiveness with which the slag fulfills its functions varies with temperature and composition. Since operating temperatures are fixed largely by the specified nature of the product and the equipment, the speed and extent to which the functions of the slag are carried out depend largely on its composition. The necessity for regulating slag composition to accomplish the re-